Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbantu Quizizz Terhadap Kemampuan Berpikir Kritis Peserta Didik - Nur Rezki Pranoto; Sudiyanto Sudiyanto (Jurnal Akuntan Publik, 2024)
This research aims to determine the influence of the guided inquiry learning model assisted by Quizzizz on students' critical thinking abilities. This research is quantitative research with an experimental design. The data sources for this research include students in class The sampling technique in this research used a cluster sampling technique and a research sample of 70 students was obtained. The samples used in the research were 35 students in class X of the Accounting and Finance expertise program at Institution 1 as the experimental group and 35 students in class Data collection techniques using test methods and documentation methods. Data analysis in the form of prerequisite tests for this research is the normality test with Kolmogrov-Smirnov and the homogeneity test with Levene Statistics. Hypothesis testing in this study was the Independent Sample T-Test with a significant value of 0.05 with the help of the SPSS Version 27 program. The results of this study concluded that there was an influence of the guided inquiry learning model assisted by Quizzizz on students' critical thinking abilities. This is indicated by a significant value of 0.014 < 0.05.